Age-Varying Association Between Statin Use and Incident Alzheimer's Disease - Li, Ge; Shofer, Jane B.; Rhew, Isaac C.; Kukull, Walter A.; Peskind, Elaine R.; McCormick, Wayne; Bowen, James D.; Schellenberg, Gerard D.; Crane, Paul K.; Breitner, John C.S.; Larson, Eric B. (Journal of the American Geriatrics Society (JAGS), 2010)
OBJECTIVES: To determine whether risk reduction of statins for Alzheimer's disease (AD) varies by age or presence of apolipoprotein E (APOE) ɛ4 allele. DESIGN: A cohort of cognitively intact elderly participants was assessed biennially for dementia and AD. SETTING: Community based. PARTICIPANTS: Three thousand three hundred ninety‐two members of a health maintenance organization (HMO) aged 65 and older and without dementia. MEASUREMENTS: Statin use was identified from the HMO pharmacy database, and proportional hazards models were applied with statin use as a time‐dependent covariate to assess the association between statins and AD and the modifying effects of age and the APOE ɛ4 allele. RESULTS: Over an average of 6.1 years of follow‐up of 3,099 participants, 263 participants developed probable AD. The adjusted hazard ratio (aHR) for statin use was 0.62 (95% confidence interval (CI)=0.40–0.97) for AD in models including demographic characteristics and vascular risk factors as covariates. The strength of the association between statins and AD diminished with age (statin‐by–age at entry interaction P=.04); the aHR in those younger than 80 was 0.44 (95% CI=0.25–0.78), versus 1.22 (95% CI=0.61–2.42) for aged 80 and older. The interaction term for statin use–by–APOE ɛ4 was not significant (P=.65). CONCLUSION: This enlarged study confirms earlier findings that statin therapy in early old age, but not in late age, may be associated with a lower risk of AD. The relationship between statin use and AD was consistent across APOE genotypes.